Equivalent own name bias in autism: An EEG study of the Attentional Blink - Nijhof, A; von Trott zu Solz, J; Catmur, C; Bird, G (Springer, 2021)
The “Attentional Blink” refers to difficulty in detecting the second of two target stimuli presented in rapid temporal succession. Studies have shown that salient target stimuli, such as one’s own name, reduce the magnitude of this effect. Given indications that self-related processing is altered in autism, it is an open question whether this attentional self-bias is reduced in autism. To investigate this, in the current study we utilised an Attentional Blink paradigm involving one’s own and others’ names, in a group of 24 autistic adults, and 22 neurotypical adults, while measuring EEG. In line with previous studies, the Attentional Blink was reduced when the participant’s own name was the second target, with no differences between autistic and neurotypical participants. ERP results show that the effect on the Attentional Blink of one’s own name was reflected in increased N2 and P3 amplitudes, for both autistic and nonautistic individuals. This is the first event-related potential study of own-name processing in the context of the Attentional Blink. The results provide evidence of an intact attentional self-bias in autism, both at the behavioural and neural level.